IMPROVING ENGLISH SPEAKING SKILL OF MEDICAL STUDENTS USING THE KNOWLEDGE OF TREE METHODS - Muxamatjonova Diyora Rustam qizi (American Journals, 2024)
Learning language is a sphere that has tremendous challenges especially dealing with the each skill. English is one of the main component of the modern education in order to be aware of the new researches and techniques at the same time to share the information that an individual made. There will below highlights the essences of the oral component to medical students. The aim of the paper is teaching medical terms with the using and reaching speaking skill in C1 level with fluency and coherence with the help of using new speaking method in the higher educations.
Keywords: Communicative competence, integration of medicine, the tree of knowledge, EFL/ESL, medical lexicology, audio dialogues.